Investigating the ways parents perceive their preschool aged children’s influence on their food purchase behaviour and brand preference - Kásler, Tímea Tina (Marketing & Menedzsment, 2020)
THE AIMS OF THE PAPER To explore to what extent children exert influence on the food purchase behaviour of their parents. The study further analyses what role brand preferences of children have on the food consumption of their families according to their parents. METHODOLOGY To obtain a deeper understanding of what brand preferences are present in the lives of preschool children and how these affect the family consumption, in-depth interviews were conducted among the parents of preschool (3-6 year-old) children in Hungary. All of the seven regions of Hungary were included in the sample, the interviews were recorded, then transcribed. The sample of size N=15 was then analysed via NVivo. The in-depth interviews were followed by an in-store observation of most participants. MOST IMPORTANT RESULTS Findings confirm that children develop preferences for brands even at such a young age. Most respondents recalled switching brands from the food and beverage industry due to their children’s preferences. Even though literature in the child consumer behaviour field is vast, research is scarce regarding this certain age group. The current study can be of great use to brand managers, to help build relationships with young consumers and their families. A robust child-brand relationship nurtured now, can help a firm develop competitive advantage in the long term. It can further be applicable in the design of product and communication strategies. RECOMMENDATIONS The current research may be supportive when considering the future of children’s food marketing and even tackling the issue of childhood obesity. The results reflected that, the majority of preferred brands by children were sweets and savoury snacks, the paper suggest numerous possible implications for public health policy makers. The paper further highlights the shifts in brand usage within families, in other words those products that families are likely to substitute once their child starts building their own relationship and brand preferences.